Key limiting factors of grain productivity in subtropical southern Chinese paddy fields from a land-health perspective - REN Xiang-ning (Journal of Agricultural Resources and Environment, 2020)
Ensuring national food security and healthy land for grain production is a priority because of changes to international agricultural supply and demand and domestic non-agricultural commodities. Considerations for cultivated land quality still focus on coupling the "natural environmental background" and "input-output" and lack a multi-dimensional perspective. Paddy field grain productivity in subtropical southern China(Conghua District, Guangzhou City) was studied to identify the key limiting factors. Sampling, on-site investigations, and production measurements were completed with a Geodetector. The three primary health dimensions that influenced paddy field grain productivity were the geographical environment health background(q=2.702), the soil health status(q=2.025), and the farmland health artificial environment(q=1.200). In total, 36 influencing factors were observed, and the contributions(q values)ranged from 0.004 to 0.537. The key limiting factors were the farmland hydrological conditions, the soil physical and trace element health status, the soil erosion status, the production security measures, and the human management intensity. Their contributions ranged from 0.299 to 0.537 in the following order:soil texture > average water level change > farming activity frequency > soil erosion degree > irrigation support capacity > available silicon content > irrigation method. Using a modern agricultural planting strategy, the soil fertility, pH, and microbial activity health levels were high, but the available silicon content was insufficient. These results suggest that managing the farmland water environment(i. e., irrigation guarantee and irrigation methods) is important. The farmland grain production capacity "barrel effect" continues to threaten food security, leading to instability and spatial differences. Therefore, soil trace elements and water management during crop growth are critical factors for land health.